Knowledge, attitudes, and practices regarding avian influenza among poultry farmers near migratory bird habitats in Guidong County, China - Jiang, Yan; Zhong, DaiJun; Han, Yang; Zhou, Yong; Zhou, HaiJian (Frontiers in Public Health, 2025)
ObjectiveTo assess the knowledge, attitudes, and preventive behaviors (KAP) regarding avian influenza among poultry farmers living near migratory bird habitats in Guidong County, China, and to identify determinants of these practices using structural equation modeling.MethodsA cross-sectional survey was conducted in July 2021 among 221 poultry farmers from three towns adjacent to migratory bird habitats. A structured questionnaire was used to collect data on KAP related to avian influenza. Descriptive statistics was used to analyze KAP levels. A structural equation model was developed with AMOS 24.0 to examine the relationships among knowledge, attitudes, and behaviors.ResultsThe overall mean KAP score was 32.97 ± 7.95 (51.5%) of maximum possible score, indicating suboptimal levels. In the fitted model, knowledge exerted both a direct effect on preventive behaviors (standardized path coefficient = 0.183) and an indirect effect mediated through attitudes (0.056). Attitude additionally influenced behavior directly (0.181). Goodness-of-fit indices confirmed robust model fit.ConclusionStudy findings indicate that poultry farmers living near migratory bird habitats in Guidong County demonstrate insufficient avian influenza–related knowledge, attitudes, and practices. Targeted health education that enhances accurate knowledge and fosters positive attitudes is critical to strengthening preventive behaviors and mitigating transmission risk.